Obesity and the accelerated decline in total sleep time increases the self-reported diagnoses of diabetes - Yan, Lijing; Sun, Huanhuan; Chen, Yuling; Yu, Xiaohui; Zhang, Jingru; Li, Peijie (Frontiers in Endocrinology, 2025)
IntroductionThe aim of this study was to investigate the relationship between obesity and the accelerated decline in Total Sleep Time (TST) and its potential impact on the self-reported diagnoses of diabetes.MethodsOur study addresses this gap by analyzing trends in a longitudinal cohort study conducted in China, using data from the China Health and Nutrition Survey (CHNS). Employing a joint model, inter-individual variability and intra-individual variability in TST, and its impact on self-reported diagnoses of diabetes were considered.ResultsOur findings reveal that self-reported diagnoses of diabetes prevalence in China rose from 1.10% in 2004 to 3.06% in 2015, accompanied by a decrease in average TST from 8.12 to 7.80. With age, TST decreased by 0.01 per year. Among coffee or tea consumers, it decreased by 0.03, while alcohol users saw a decrease of 0.07. The obese group experienced a decrease of 0.05, the overweight group 0.03, and the normal weight group 0.01. Each 1-hour decrease in TST was associated with a substantial 3.61-fold increase in self-reported diagnoses of diabetes risk (95% CI: 2.92-4.44). Specifically, individuals with a higher baseline TST tend to experience smaller changes over time, whereas those with a lower baseline TST tend to experience larger changes.DiscussionFor the obese, TST decreases at an accelerated rate which contributes to the risk of self-reported diagnoses of diabetes. The findings underscore the role of sleep loss in diabetes risk, with implications for public policy. Future research and interventions should emphasise the impact of sleep management, particularly on obesity and metabolic health, to develop more effective prevention and treatment strategies.